Multiliteracies meet new methods: The case for digital writing in English education case study in G-7 countries. - Xiaoying Hu (PLoS ONE)
Recently, globe has tried to transform populace activities to digital platform, wherefrom all stakeholders can attain their basic information. However, education sector cannot be excluded from this debate. Since, the pandemic mostly most economies have utilized digital transformation in different aspects of life, but digital education becomes more prominent. Therefore, this empirical research focuses on digital writing specifically to English education in G-7 economies between the time frame spanning from January 2000 to April 2022. This study considers urbanization, income, renewable energy, information & communication technology, renewable energy, English education, and pandemic as the key environmental determinants. To address the challenges posed by panel data, this study utilized an advanced set of estimators such as AMG stands for Augmented Mean Group. The estimate of urbanization and income per capita is positively significant, confirming that urbanization and economic development cannot protect the green economy by minimizing environmental pollution. Likewise, the estimated coefficient of English Education and internet use is negative and significant, implying that English Education and ICT can protect the green economy by reducing emissions. Conversely, renewable energy consumption (REC) is an element that can increase economic activity and therefore decline the environmental damages to secure a green economy. Likewise, the growth in cases of Covid-19 also reduces the usage of resources like land, water, and forests and subsequently decreases carbon emissions, promoting the green economy. The results also indicate that interaction term of English Education and ICT have adverse impact on Carbon emission (CO2). The outcomes suggest that internet usage (ICT) in English Education (EE) can deal efficiently with environmental issues for the green economy; therefore, EE and ICT should be part of green policies across the international level.